2019
DOI: 10.1051/0004-6361/201935279
|View full text |Cite
|
Sign up to set email alerts
|

Extreme hydrodynamic losses of Earth-like atmospheres in the habitable zones of very active stars

Abstract: Aims. In this letter, we calculate for the first time the full transonic hydrodynamic escape of an Earth-like atmosphere. We consider the case of an Earth-mass planet with an atmospheric composition identical to that of the current Earth orbiting at 1 AU around a young and very active solar mass star. Methods. To model the upper atmosphere, we used the Kompot Code, which is a first-principles model that calculates the physical structures of the upper atmospheres of planets, taking into account hydrodynamics an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 29 publications
1
67
1
Order By: Relevance
“…Moreover, Airapetian et al (2017b) found that the escape time of a 1 bar atmosphere on a terrestrial-type planet in the habitable zone of Proxima Cen b is expected to be about 10 Myr. In agreement with these results, a more recent study by Johnstone et al (2019) found extreme hydrodynamic losses of Earth-like at-mospheres in the habitable zones of very active stars, resulting in the complete evaporation of a modern Earth atmosphere in £ 0.1 Myr. One can conclude that atmospheres of M and K star Earth-like habitable zone planets, which could maintain liquid water oceans on their surface, are unlikely to build up N 2 -dominated atmospheres.…”
Section: Earth-like Planets In Habitable Zones Of M-and K-type Starssupporting
confidence: 79%
“…Moreover, Airapetian et al (2017b) found that the escape time of a 1 bar atmosphere on a terrestrial-type planet in the habitable zone of Proxima Cen b is expected to be about 10 Myr. In agreement with these results, a more recent study by Johnstone et al (2019) found extreme hydrodynamic losses of Earth-like at-mospheres in the habitable zones of very active stars, resulting in the complete evaporation of a modern Earth atmosphere in £ 0.1 Myr. One can conclude that atmospheres of M and K star Earth-like habitable zone planets, which could maintain liquid water oceans on their surface, are unlikely to build up N 2 -dominated atmospheres.…”
Section: Earth-like Planets In Habitable Zones Of M-and K-type Starssupporting
confidence: 79%
“…As known from the Sun there is interaction between CMEs and the Earth's atmosphere. Model results for exoplanet systems have shown that frequent and energetic CMEs together with a high short-wavelength (EUV) radiation environment lead to very efficient planetary atmospheric mass loss (Lammer et al 2007;Khodachenko et al 2007;Cohen et al 2011;Cherenkov et al 2017;Johnstone et al 2019). In a worst-case scenario frequent and energetic CME impacts may lead to the loss of planetary atmospheres and therefore CMEs endanger planetary habitability.…”
Section: Introductionmentioning
confidence: 99%
“…at the equator, in order to provide the case of maximum irradiance. Very recently, it was predicted that Earth-like atmospheres can not form in the habitable zones of very active stars (Johnstone et al 2019), and atmospheres containing CO 2 are likely stable on waterdepleted planets orbiting M dwarfs (Gao et al 2015). Atmospheres dominated by N 2 tend to be unstable under high XUV fluxes and experience efficient atmospheric escape (Tian et al 2008;Lammer et al 2011).…”
Section: Estimation Of Uv Surface Fluxes During Quiescent Stellar Conmentioning
confidence: 99%
“…The effectiveness of UVA to induce lethal damage depends also on mechanisms that in the presence of oxygen produce reactive oxygen species (Kielbassa et al 1997;Oppezzo et al 2011). According to several studies O-rich atmospheres are not expected to exist in planets orbiting M-type stars (Garcia-Sage et al 2017;Johnstone et al 2019), therefore, this would reduce the damage induced by UVA in this context.…”
Section: Uv Radiation On the Planetary Surfacementioning
confidence: 99%
See 1 more Smart Citation